SHAPING NEW BOUNDARIES AN ANALYTICAL SYMPHONY ON TECHNOLOGICAL ADVANCEMENTS IN CORPORATE, NON-PROFIT SECTORS AND SOCIAL ENTREPRENEURSHIP - Hegde S, Vidyadhara; S, Ganesha; Shetty K, Udaya; P, Sudarshan; Thoti, Kiran Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Investigation to provide a comprehensive and illuminating picture of the dynamic scene formed by technology progress at the crossroads of social entrepreneurship and business. To get relevant results from the vast Scopus database, the study painstakingly uses a sophisticated search approach, inserting terms like "technology," "innovations," and "business" into the intricate web of ever-growing body of literature. A modern and representative dataset, suitable for in-depth study, is assured by this careful curation process. This study aims to do more than just identify trends; it will also investigate different document types, identify notable authors, identify influential source titles, identify primary themes within the ever-changing field of social entrepreneurship, and more. The analysis quantitatively examines publication trends, citation counts, and complex keyword co-occurrence patterns using a rigorous and thorough methodology. The study uses cutting-edge visualization methods to create a detailed map of the research environment, showing how different areas of study are connected and grouped together based on themes. From the revolutionary effect of AI on company models to the favourable relationship between technical innovation and the creation of jobs in small enterprises, the synthesis findings culled from influential studies cover a wide range of subjects. The study also elucidates the significance of innovation in reaching sustainability targets, the continuous digitization of company models, and the revolutionary impact of FinTech on the conventional financial services industry. Ultimately, this extensive bibliometric study makes a strong case for a more organized, sophisticated, and illuminating comprehension of technical advancements in the complex domains of social and corporate entrepreneurship. By providing an up-to-date and thorough overview of the changing scene and by naming and recognizing important players, it enhances the conversation around this dynamic juncture. Because of its comprehensive nature, the research is an excellent tool for academics, professionals, and politicians who are interested in learning about and making a difference at the revolutionary crossroads of social entrepreneurship, technology, and commerce.